y = x + 4/x
replace x with -x. Do you get back the original equation after simplifying. if you do, the function is even. replace y with -y AND x with -x. Do you get back the original equation after simplifying. If you do, the function is odd. A function can be either even or odd but not both. Or it can be neither one. Let's first replace x with -x
y = -x + 4/-x = -x - 4/x = -(x + 4/x)
we see that this function is not the same because the original function has been multiplied by -1 . Let's replace y with -y and x with -x
-y = -x + 4/-x
-y = -x - 4/x
-y = -(x + 4/x)
y = x + 4/x
This is the original equation so the function is odd.